Design Rhetoric with Anneli Bowie (South Africa) - Bjork C; Quintero J; Bowie A (Global Rhetorics Podcast, 2020)
Producer-hosts Dr Collin Bjork and Jose Quintero interview Dr Anneli Bowie. This episode features an interview with Dr. Anneli Bowie, a scholar at the University of Johannesburg in South Africa. She discusses her research at the intersection of design and rhetoric. She also describes her time as an Erasmus Mundus scholar in Sweden, her service learning pedagogy, and her latest research about the Fourth Industrial Revolution.